2017
DOI: 10.1016/j.jcjo.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Current indications and surgical approaches to corneal transplants at the University of Toronto: A clinical-pathological study

Abstract: Almost two-thirds of all corneal transplant procedures at the University of Toronto are partial thickness procedures. A failed graft was found to be the most common indication for full-thickness transplants. Fuchs' dystrophy was the most common indication for a partial-thickness approach, most often treated by DSAEK. Longitudinal data are needed to determine whether partial-thickness surgeries will improve graft survival and reduce the need for regraft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 38 publications
3
33
2
1
Order By: Relevance
“…FECD was managed by DSAEK in 83 per cent cases and PKP in 13 per cent in 2011-2012. Le et al 30 evaluated the current surgical approaches at the University of Toronto and found that 61 per cent of keratoplasties were LK and 39 per cent underwent full-thickness PKP. Amongst the lamellar procedures, DSAEK accounted for most of the surgeries (68%) followed equally by DALK (16%) and DMEK (16%).…”
Section: Review Of Literature: Changing Trendsmentioning
confidence: 99%
See 2 more Smart Citations
“…FECD was managed by DSAEK in 83 per cent cases and PKP in 13 per cent in 2011-2012. Le et al 30 evaluated the current surgical approaches at the University of Toronto and found that 61 per cent of keratoplasties were LK and 39 per cent underwent full-thickness PKP. Amongst the lamellar procedures, DSAEK accounted for most of the surgeries (68%) followed equally by DALK (16%) and DMEK (16%).…”
Section: Review Of Literature: Changing Trendsmentioning
confidence: 99%
“…According to Le et al 30, the most common indication for PKP was graft failure (30%) followed by infection (18%), and keratoconus (17%). DSAEK was most commonly done for FECD (40%) and bullous keratopathy (33%).…”
Section: Review Of Literature: Changing Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, older patients are less likely to have frequent rejection episodes, as their immune systems are not as strong as young patients. 39 , 40 , 41 The most common indication for DALK is keratoconus, 42 and these patients tend to be younger. Hence, in comparison to PK, DALK offers an advantage of reduced chances of rejection.…”
Section: Resultsmentioning
confidence: 99%
“…[2] Leading indications for keratoplasty and implemented surgical techniques vary from one country to another depending on their geographic regions, socioeconomic conditions, and adaptation to recent surgical technological advancements. [3][4][5][6][7][8][9][10][11] For instance, in developed countries, bullous keratopathy (BK) and Fuchs' endothelial dystrophy (FED) are the leading indications for keratoplasty, and with the adaptation of endothelial keratoplasty (EK) techniques in these countries, Descemet stripping automated endothelial keratoplasty (DSAEK) and Descemet membrane endothelial keratoplasty (DMEK) are the procedures of choice to selectively replace the diseased corneal endothelium. [4][5][6][7][8]11] However, the leading indications for keratoplasty in developing countries vary from keratoconus (KCN) in Iran and Zimbabwe [3,12,13] to infectious keratitis and corneal scarring in China and India.…”
Section: Corneal Blindness Is the Third Leading Cause Of Avoidable VImentioning
confidence: 99%